The dynamics of the index of endogamy and the level of inter-ethnic marriages in the district populations of Kherson region - Лановенко, О. Г. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2014)
At conducting population-genetic studies of contemporary rural population of Kherson region the whole area should be considered as measures of an elementary population (the index of endogamy is 0,54–0,81). Only Gornostaivskyi district matches the criterion of elementary population at the district level (percentage of endogamous marriages is 57.0%). All regional centers, except the city Berіslav are basic population units at the district level (the index of endogamy is 0,50–0,62) with relatively stable for 54 years level of inter-ethnic marriages (30,1–29,1 %). For village councils elementary population unit is the whole area (the index of endogamy is 0,64–0,80). The general trend is increase of the proportion of inter-ethnic marriages both in the districts as a whole (from 30.5 to 32.4%) and within village councils (from 30.9 to 35.7%). In Gornostaivskyi district on the background of declining proportion of inter-ethnic marriages and increasing endogamy for the past 13 years it has been stated relative decrease of baby birth defects, stillbirth, miscarriages, probably due to the formation of adaptive complexes of genes that counteract the effects of genetic drift. Revealed patterns require further study.